One-dimensional inverse power reflectionless potentials V(x) = const│x-x₀ │⁻ⁿ - Maydanyuk, S.P. (Вопросы атомной науки и техники, 2004)
A condition, at which inverse power one-dimensional potential becomes reflectionless during propagation through it of a plane wave, is obtained on the basis of SUSY QM methods. A scattering of a particle on spherically symmetric potential is analysed with taking into account of the reflectionless possibility.